First principles studies on properties of Pb(II), Sn(II) and Ge(II) ferroelectric materials using density functional theory / Mohamad Fariz Mohamad Taib - Mohamad Taib, Mohamad Fariz (Institute of Graduate Studies, UiTM, 2015)
Quantum calculations via the first-principles study using the density functional theory (DFT) have offered great opportunities to describe the origin and most fundamental properties of new materials. In addition, detailed properties of the materials can be visualized by providing an accurate view at the atomic level. In this study, works are focused on investigating new lead-free ferroelectric materials that have a similar special ns2 lone pair electrons with Pb (II) such as Sn (II) and Ge (II) via first principles calculation. Modification of Pb-based materials (PTO and PZT) by substituting or doping at the A-site are numerically anticipated to enhance the ferroelectric properties as well as to eventually reduce the consumption of Pb (II) in electroactive devices. Properties of lead-based materials PbTiO3 (PTO), PbZrO3 (PZO) and PbZrTiO3 (PZT) as reference materials were compared with new lead-free ferroelectric materials such as SnTiO3 (SnTO), GeTiO3 (GTO) and SnZrO3 (SnZO). All calculations were performed using first principles study based on Density Functional Theory (DFT) that has been implemented in CASTEP computer code. Functional GGA-PBEsol exhibits the most accurate values for lattice parameter with 0.6 % relative to experimental values for both cubic PbTiO3 and PbZrO3 (reference materials). Meanwhile, LDA-CAPZ functional is accurate for tetragonal PTO…